Fundamentos Técnicos do Tiro de Duelo - Rosa, Alberto Gomes Santa; Vaz, Robesio da Costa; Rodrigues, David; Viana Filho, Humberto de Azevedo; Perez, Victor Edgar; Varela, Romualdo (Revista de Educação Física / Journal of Physical Education, 2021)
Resumo do artigo "Fundamentos Técnicos do Tiro de Duelo"